Evaluasi Program Diklat Manajemen Usaha Tata Boga Berbasis Pastry dan Bakery di Balai Pendidikan dan Pelatihan Koperasi UMKM Mataram - Wiryawan, I Nyoman Angga; Rizka, M. Arief (Program Studi Pendidikan Luar Sekolah, 2024)
Abstract: This research aims to evaluate the context to find out the purpose of organizing training, evaluate input, to find out the training space provided to support the training process, to find out if the instructor can help the training process in delivering the material well, to find out whether the equipment provided for training is adequate, to evaluate the process, to knowing that the training material can be well received by training participants, product evaluation, to find out that the training program can help participants improve their culinary skills. This research uses a quantitative evaluative method with the CIPP (Context, Input, Process, Product) evaluation model. The sample was determined using proportional sampling with a population of 50 people and 25 research subjects. The data collection techniques used were questionnaires, interviews and documentation. The analysis method used is the Likert scale percentage. The results of the Likert percentage analysis show that the context component is in the very effective category, namely 90.40%, the input component is in the very effective category, namely 93.48%, the process component is in the very effective category, namely 92.57, and the product component is in the very effective category, namely 97.37%. The average percentage result of the 4 aspects, namely 93.37, is in the very effective category. So it can be concluded that the evaluation of the pastry and bakery-based culinary business management training program at the UMKM Cooperative Education and Training Center, Mataram, West Nusa Tenggara is in the very effective category.Keywords: Program Evaluation, Management Training, Education and TrainingAbstrak: TujuanÂ penelitian ini adalahÂ evaluasi context untuk mengetaui tujuan penyelenggaraan diklat, evaluasi input, ntuk mengetahui ruang pelatihan yang disediakan mendukung proses diklat, untuk mengetahui instruktur dapat membantu proses diklat dalam menyampaikan materi dengan baik, untuk mengetahui peralatan yang disediakan untuk diklat memadai, evaluasi process, untuk mengetahui materi pelatihan dapat diterima dengan baik oleh peserta diklat, evaluasi product, untuk mengetahui program diklat dapat membantu para peserta meningkatkan keterampilan tata boga. Penelitian ini menggunakan metode kuantitatif evaluatif dengan model evaluasi CIPP (Context, Input, Process, Product). Penentuan sampelnya menggunakan porposive sampling dengan jumlah populasi 50 orang dan subyek penelitian 25 orang. Adapun teknik pengumpulan data yang digunakan yaitu angket, wawancara dan dokumentasi. Metode analisis yang digunakan yaitu persentase skala likert. Hasil dari analisis persentase likert menunjukan bahwa komponen context masuk dalam kategori sangat efektif yakni 90,40%, komponen input masuk dalam kategori sangat efektif yakni 93,48%, komponen process masuk dalam kategori sangat efektif yakni 92,57, dan komponen product masuk dalam kategori sangat efektif yakni 97,37%, Hasil rata rata persentase dari ke 4 aspek yaitu 93,37 masuk dalam kategori sangat efektif. Jadi dapat disimpulkan bahwa, evaluasi program diklat manajemen usaha tata boga berbasis pastry dan bakery di Balai Pendidikan dan Pelatihan Koperasi UMKM,Mataram, Nusa Tenggara Barat masuk dalam kategori sangat efektif.Kata Kunci:Â Evaluasi Program, Diklat Manajemen, Pendidikan dan Pelatihan